The New (Ab)Normal Reshaping Business and Supply Chain Strategy Beyond Covid-19 - Sheffi, Yossi (Transoft Inc., 2020)
Much has been written about Covid-19 victims, how scientists raced to understand and treat the disease, and how governments did (or did not) protect their citizens. Less has been written about the pandemic's impact on the global economy and how companies coped as the competitive environment was upended.In this book, The New (Ab)Normal, MIT Professor Yossi Sheffi maps how the Covid-19 pandemic impacted business, supply chains, and society. He exposes the critical role supply chains play in helping people, governments, and companies to manage the crisis. The book draws on executive interviews, pandemic media coverage, and historical analyses. Sheffi also builds on themes from his books The Resilient Enterprise (2005) and The Power of Resilience (2015) to suggest how companies can become more resilient in the face of uncertainty. The author paints a compelling picture of how the Covid-19 virus is changing many facets of human life and what our post-pandemic world might look like. This must-read book helps companies and entrepreneurs to redefine their business models and adjust to a fast-evolving economic landscape